Consequences of Exposure to Violence, Aggression, and Sexual Harassment in Private Security Work: A Mediation Model. Issue 11 (June 2022) - Herrmann, Alexander; Seubert, Christian; Glaser, Jürgen
While exposure to violence and aggression is well known for its detrimental effects on employees' health as well as organizational outcomes, certain high-risk work domains have scarcely been researched. Thus, this study set out to determine negative consequences of work-related exposure to four forms of harmful behaviors in private security. In a sample of 487 German-speaking security guards, 23% had experienced outsider-initiated violence, 56% aggressive acts, 30% vicarious violent acts, and 3% were sexually harassed over the past 12 months. Additionally, 19% reported substantial to extreme worries about violence. By presenting an integrated model of negative consequences to outsider-initiated violent, aggressive as well as sexual harassing acts, we strived to extend previous research by showing that turnover intention (as an ultimate negative behavioral outcome) is only indirectly related to these experiences via worries about violence and psychosomatic complaints. Structural equation modeling provided support for the model and plausibility for a sequential "two-step" prediction of turnover intention. Further, we provided support that worries about violence are not solely triggered by directly experiencing physical violence but also vicarious violence, aggressive acts, and sexual harassment. Consistent with previous studies, worries about violence were identified as a central mediator in the transmission process from exposure to harmful behaviors at work to negative consequences, that is, psychosomatic complaints and turnover intention. Our findings have implications for the detailed understanding of consequences emerging from exposure to workplace violence and aggression as well as the development of effective prevention strategies especially in high-risk occupations such as private security.